Những câu hỏi liên quan
PB
Xem chi tiết
CT
28 tháng 6 2017 lúc 14:55

Biến đổi VP

=> VT = VP

=> Đpcm

Bình luận (0)
DV
Xem chi tiết
NT
5 tháng 10 2021 lúc 21:24

\(\left(a+b\right)^3-3ab\left(a+b\right)\)

\(=\left(a+b\right)\left(a^2-ab+b^2\right)\)

\(=a^3+b^3\)

Bình luận (0)
AH
5 tháng 10 2021 lúc 21:26

Lời giải:

$(a+b)^3-3ab(a+b)$

$=a^3+3a^2b+3ab^2+b^3-(3a^2b+3ab^2)$

$=a^3+b^3$
Ta có đpcm.

Bình luận (0)
DV
Xem chi tiết
NM
5 tháng 10 2021 lúc 20:36

\(VP=\left(a+b\right)^3-3ab\left(a+b\right)=a^3+3a^2b+3ab^2+b^3-3a^2b-3ab^2=a^3+b^3=VT\)

Bình luận (0)
LL
5 tháng 10 2021 lúc 20:36

\(\left(a+b\right)^3-3ab\left(a+b\right)=a^3+b^3+3a^2b+3ab^2-3a^2b-3ab^2=a^3+b^3\left(đpcm\right)\)

Bình luận (0)
NT
5 tháng 10 2021 lúc 20:41

\(\left(a+b\right)^3-3ab\left(a+b\right)\)

\(=\left(a+b\right)\left(a^2+2ab+b^2-3ba\right)\)

\(=a^3+b^3\)

Bình luận (0)
DV
Xem chi tiết
NT
5 tháng 10 2021 lúc 21:28

\(\left(a+b\right)^3-3ab\left(a+b\right)\)

\(=\left(a+b\right)\left(a^2+2ab+b^2-3ab\right)\)

\(=\left(a+b\right)\left(a^2-ab+b^2\right)\)

\(=a^3+b^3\)

Bình luận (0)
AD
Xem chi tiết
NT
5 tháng 1 2023 lúc 21:43

(a-b)^2=(a-b)(a-b)=a^2-ab-ab+b^2=a^2-2ba+b^2

(a-b)(a+b)=a^2+ab-ab-b^2=a^2-b^2

(a+3)^3=(a+b)^2*(a+b)

=(a^2+2ab+b^2)(a+b)

=a^3+a^2b+2a^2b+2ab^2+b^2a+b^3

=a^3+3a^2b+3ab^2+b^3

Bình luận (0)
H24
Xem chi tiết
H24
Xem chi tiết
H24
Xem chi tiết
H24
Xem chi tiết
NM
13 tháng 10 2021 lúc 15:55

\(2,\\ a,a^3+b^3=a^3=3a^2b+3ab^2+b^3-3a^2b-3ab^2\\ =\left(a+b\right)^3-3ab\left(a+b\right)\\ b,a^3+b^3+c^3-3abc\\ =\left(a+b\right)^3-3ab\left(a+b\right)+c^3-3abc\\ =\left(a+b+c\right)\left(a^2+2ab+b^2-ac-bc+c^2\right)-3ab\left(a+b+c\right)\\ =\left(a+b+c\right)\left(a^2+b^2+c^2-ac-ab-bc\right)\)

Bình luận (0)
MS
13 tháng 10 2021 lúc 16:10

khó v. e ko giải đc đâu

 

Bình luận (1)
H24
Xem chi tiết